STRATEGI KOMUNIKASI PEMERINTAHAN WALIKOTA TEGAL DALAM PENANGGULANGAN PANDEMI COVID-19 - Sri Sutjiatmi; Dimas Purbo Pambudi; Erny Rosyanti; Vina Amelia; Akhmad Habibullah (Universitas Prof. Dr. Moestopo (Beragama), 2022)
This study focuses on government communication strategy of Mayor’s Tegal city to mitigating covid-19 pandemic. This research was conducted to identify and describe the communication strategy that used Dedy Yon Supriyono to leads covid-19 pandemic mitigation. This research uses a qualitative approach with a case study methodology through in-depth interviews as the primary data collection method. The theory used in this study is communication strategy. The results of this study indicate that communication strategy of the Tegal Mayor's administration has been effective starting from the research, planning, implementation, evaluation, to reporting stages. All leading sectors have been maximal in coordinating in covid-19 pandemic mitigation based on Peraturan Daerah Nomor 10 Tahun 2020 tentang Penanggulangan Corona Virus Disease 2019 and supported with various media such as websites and instagram.